IODP Drilling of the "Shackleton Sites" on the Iberian Margin: A Plio-Pleistocene Marine Reference Section of Millennial-Scale Climate Change - F. Abrantes; D. Hodell; G. Carrara; L. Batista; H. Duarte (Scientific Drilling, 2010)
No abstract available. doi:10.2204/iodp.sd.9.10.2010